2023
DOI: 10.1063/5.0143892
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric phase transitions in epitaxial antiferroelectric PbZrO3 thin films

Abstract: The archetypical antiferroelectric, PbZrO3, is currently attracting a lot of interest, but no consensus can be clearly established on the nature of its ground state as well as on the influence of external stimuli over its physical properties. Here, the antiferroelectric state of 45-nm-thick epitaxial thin films of PbZrO3 is established by observing the characteristic structural periodicity of antiparallel dipoles at the atomic scale, combined with clear double hysteresis of the polarization-electric field resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…At 300 °C, the P–E loop exhibits paraelectric behavior, suggesting the absence of antiferroelectricity upon heating. [ 47 ] Simultaneously, the remnant polarization begins to increase around this temperature, signifying a phase transition. Consequently, the PbZrO 3 thin film appears to undergo a transition from an antiferroelectric to a paraelectric state at 300–325 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 300 °C, the P–E loop exhibits paraelectric behavior, suggesting the absence of antiferroelectricity upon heating. [ 47 ] Simultaneously, the remnant polarization begins to increase around this temperature, signifying a phase transition. Consequently, the PbZrO 3 thin film appears to undergo a transition from an antiferroelectric to a paraelectric state at 300–325 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the PbZrO 3 thin film appears to undergo a transition from an antiferroelectric to a paraelectric state at 300–325 °C. Note that the Curie temperature (T c ) of bulk PbZrO 3 is reported to be 230 °C, [ 47 ] the difference in T c observed may be attributed to the presence of residual stress between the film and substrate. In the case of (Pb 1−X Ba X )ZrO 3 thin film with X = 0.02, as displayed in Figure 4b, a phase transition similar to that of X = 0 was observed, albeit with a transition temperature found to be approximately between 275 and 300 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Since the R reflection corresponds to oxygen octahedron tilts and the � reflection corresponds to lead atom displacements, different field kinetics of these two orderings can be assumed here. The different behavior of different orderings is an interesting result which has also been discussed in temperature-induced phase transitions in PbZrO 3 thin films (Dufour et al, 2023). Corker et al (1997) also discussed the existence of several different antiferrodisortive (AFD) domains within one AFE domain.…”
Section: Separation Of Order Parametersmentioning
confidence: 93%
“…This manifests a new phase as an intermediate AFE state before the AFE to PE phase transition [17]. In contrast, Dufour et al [79] recently re-examined this phase transition but revealed another FE-like state that emerges in a large temperature window (100 K). From their results, transmission electron microscopy (TEM) revealed the atomic-scale high temperature polar structure, which is further supported by atomistic simulations.…”
Section: Temperature-driven Transitionsmentioning
confidence: 99%